ANALISIS PENGARUH PARTISIPASI SANTRI KOMITMEN DAN KEMAMPUAN BERINOVASI TERHADAP KINERJA KOPERASI PONDOK PESANTREN DI KOTA SEMARANG - Syarbani, Hasyim (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2012)
In order to improve the performance of cooperative boarding lodge, then it can be done with meningkatkann participation and commitment of members, because of the participation and commitment affect the performance of the company. whereas innovation-oriented company providing a positive impact on company performance. Therefore, this study is a replication of research Johanis W dominoes is applied to the cooperative boarding lodge. While the purpose of the research goal is to determine the effect of participation and ability to innovate komimen effect on the performance of cooperative boarding lodge. Based on the results show Ahwa: Turnout santri the ability to innovate cooperative commitment of the boarding lodge is still low as well as the performance cooperative boarding lodge is still low, this is indicated by a decline in business, number of members and the rest of the results of cooperative efforts boarding lodge per year. The goodness of fit indices and regression weights can be accepted research model means that the participation of santri, commitment and ability to innovate affect the performance of cooperative boarding lodge. So it can be concluded that the low performance of cooperatives that santri affected by the lack of participation, commitment and ability to innovate cooperative boarding lodge.